2003
DOI: 10.1016/j.jvs.2003.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Durability and cumulative functional patency of transposed and nontransposed arteriovenous fistulas

Abstract: Preoperative duplex scanning of upper arm and forearm veins facilitated successful creation of all types of autogenous fistulas at our institution. TAVF cumulative functional patency rates were superior compared with AVGs and AVFs. Furthermore, TAVFs and AVFs were more durable and required fewer revisions than did AVGs. When preoperative duplex criteria indicate that TAVFs can be performed, they should be the initial access of choice, because of their superior long-term patency and durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…Their review noted a wide range of AVF-T outcomes reported by other authors. 22,39,40 Our study found that preoperative ultrasound examination by the operating surgeon and selective use of staged procedures resulted in successful, reliable, and durable AVF-Ts in a large majority of these challenging patients.…”
Section: Discussionmentioning
confidence: 66%
“…Their review noted a wide range of AVF-T outcomes reported by other authors. 22,39,40 Our study found that preoperative ultrasound examination by the operating surgeon and selective use of staged procedures resulted in successful, reliable, and durable AVF-Ts in a large majority of these challenging patients.…”
Section: Discussionmentioning
confidence: 66%
“…15,16 During the study period, we performed 216 upper arm autogenous access procedures and less than 50% of patients met our inclusion criteria. In other words, the results of this study may be applicable to only approximately half of real life patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular access procedures and their complications are major cause of morbidity, hospitalization and cost for patients receiving long-term hemodialysis, [3] yet it is vital to this form of renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%